Effect of ginger kombucha consumption on blood pressure in patients with essential hypertension - Herianto Bangun; Hartaulina Saragih (AcTion: Aceh Nutrition Journal, 2025)
Essential hypertension remains a major global public health problem that requires effective non-pharmacological management strategies. Fermented functional beverages rich in antioxidants, such as ginger kombucha, have been proposed as potential complementary interventions for blood-pressure control. This study aimed to evaluate the effects of ginger kombucha consumption on blood pressure in patients with essential hypertension. A quasi-experimental pretest–posttest control group design was conducted involving 62 patients with hypertension at Medan Adventist Hospital, Indonesia, in April 2025. Participants were allocated to an intervention group (n = 31), which consumed 200 mL ginger kombucha twice daily for 14 days, and a control group (n = 31), which received no intervention. Blood pressure was measured using a standardized digital sphygmomanometer. Data were analyzed using paired and independent t-tests. The intervention group demonstrated a significant reduction in both systolic and diastolic blood pressure, with mean decreases of 16.2 mmHg and 10.1 mmHg, respectively (p < 0.001), whereas the changes in the control group were not statistically significant. Between-group comparisons showed significantly greater reductions in blood pressure in the intervention group (p < 0.05), indicating a clinically meaningful effect over a short period. In conclusion, ginger kombucha consumption significantly reduced blood pressure in patients with essential hypertension and may serve as a complementary non-pharmacological strategy for hypertension management. Ethical approval was obtained prior to data collection, and all the participants provided written informed consent.